Hubungan Kesinambungan Pelayanan (Continuity Of Care) Terhadap Kualitas Hidup Pasien Dengan Masalah Kardiovaskular - Hasanah, Izzahtul; Dewi, Wan Nishfa; Damanik, Siti Rahmalia (Universitas Pahlawan Tuanku Tambusai, 2024)
Continuity of care is a consistent and interconnected service provided from time to time according to patient needs. This study aims to determine the relationship between the implementation of continuity of care and the quality of life of patients with cardiovascular problems. This study used a quantitative correlation design with a cross-sectional approach. The sample of this study amounted to 87 respondents with a diagnosis of coronary heart disease 71 respondents and heart failure 16 respondents selected using purposive sampling technique. Continuity of care variables were measured using the Patient Continuity of Care Questionnaire (PCCQ) and quality of life was measured using the World Organization Quality of Life-BREF (WHOQOL-BREF) questionnaire. Data were analyzed using the Chi Square test. Data on respondent characteristics showed that the majority of respondents were aged 56-65 years (46.1%), male gender (79.3%), high school education (66.7%). The results of this study showed that the continuity of care with high significant results (63.2%) and the quality of life of patients with good conditions (52.9%). The results of bivariate analysis showed a substantial relationship between continuity of care and patient quality of life with a coefficient value of p value (0.001). The results of this study indicate that health workers play an important role in ensuring the continuity of health services at all levels. With the continuity of services, it is expected that there will be a decrease in recurrence in patients with cardiovascular problems, especially patients with coronary heart disease and heart failure.